Regional Development Differences in Hungary and the Northern-Great Plain Region - Harsányi, Endre; Harsányi, Gergely; Nagy, Attila János (Acta Agraria Debreceniensis, 2005)
The most important endeavour of European Union’s regional policy is to moderate disparities. An emphasised strategic objective of member states, based on the principle of solidarity, fairness and justice, is to develop regions and almost forty percent of the common budget is devoted to achieving this objective. Hungary, as a full EU member state, will get a new chance for underdeveloped regions, especially for the Eastern-Hungarian as well as the North Hungarian and North Plain Region. The differences in development among the regions are significantly influenced by the economic characteristics of the specific region, quality and quantity of human resources, accessability of the region and other factors influencing local quality of life beside natural conditions. The new spatial structure was formed by change of regime, processes of the nineties, primarily the economic renewal based on foreign capital investments and the crisis phenomena in parallel with these. The economic, political and social consequences of the transformation significantly changed spatial structure and increased disparities. New disparities formed which were further aggravated as a consequence due to the formation of the eastern-western slope and local crisis zones. As a result of the outstanding development of the capital, the long term differentiation of regional development differences can also be detected when examining the regional distribution of Hungarian gross domestic product. The collapse of heavy industry and agricultural mass production based on the eastern markets primarily affected the north-east counties in the eastern part of the country. Strengthening regional competitiveness is of key importance for the region, which requires the application of consistent development policy. The most important is economic development which, if it operates well, also infers the possibility of establishing welfare infrastructures. Drawing in external sources to ease the significant lack of capital is important for the processing industry and the development of supplier networks. Agricultural development also plays an important role in transforming economic structure, since the characteristics of the region, its traditions and long term competitive advantages are favourable, therefore it is going to represent a higher ratio within the economy than the EU average. The modernisation of the agricultural sector can be promoted by supporting market accession, quality agricultural production and stimulating producer-retailer cooperation. The development of transportation and informatics infrastructure as well as human resource development plays a significantly important role in the development of the region. In conclusion, the implementation of such a consistent regional development policy is required in the future, based on the strengths of the region, that serves the most efficient utilisation of regional development funds through the implementation of regional policy principles and prevents the irreversible decay of the region while promoting rapid development.